Edukasi Penatalaksanaan Diabetes terhadap Manajemen Perawatan Diri Pasien Diabetes Mellitus Tipe II - Mursidah Dewi; Yellyanda Yellyanda; Dira Ulfa (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of diabetes management education on self-care management of type II diabetes mellitus patients in the work area of the Kandis Public Health Center. The research design used in this study was quantitative with a pre-test design and a post-test approach with one group design. The results showed that there was a significant level of self-care management with a p-value of 0.000 using the paired sample t-test after receiving the Summary of Diabetes Self Care Activity (SDSCA) intervention through leaflets and flipcharts. In conclusion, there is an effect of diabetes management education on self-care management in type II diabetes mellitus patients in the Kandis Health Center Work Area, Merangin Regency. Keywords: Diabetes Mellitus, Education, Self Care